Electroactive nanomaterials for environmental and pharmaceutical sensing - Abdullah, Ibrahim Hassan (AUC Knowledge Fountain, 2019)
Sensing is an important emerging technology in the current industrial era. It covers a plethora of applications from medical personalized devices to aerospace oxygen level detectors. Of those applications, environmental and pharmaceutical sensors are significantly important. Specifically, electrochemical sensors are easy to use and develop besides being cost-effective and accurate. The work in this thesis concerns the development of two sensing platforms for the detection of Hg(II) as a water pollutant, and the detection of Lornoxicam (LOR) as a pharmaceutical compound. The materials fabricated were morphologically, structurally, and electrochemically characterized. They were also tested against their analytical targets in spiked and real sample media to ensure their utility, sensitivity and accuracy. The testing results were either in the sub-nano or the pico-molar levels, with high linear range. The materials were also examined to target the analyte species in separate and co-formulated media to assure their selectivity. Furthermore, the sensing platforms were repeatedly used to test their stability and reproducibility. Titania nanotubes/reduced graphene oxide (TNTs/RGO) showed an efficient sensibility of Hg(II) in the presence of Cu(II) and Mn(II) species with no significant interference for a wide range of concentrations. On the other hand, BaNb2O6 nanofibers showed an enhanced activity towards the electrocatalytic oxidation of Lornoxicam (LOR) and paracetamol (PAR), producing remarkably high oxidation currents. Wide linear dynamic ranges, high sensitivity, very low LOD, good reproducibility and repeatability, and high stability, together with simple procedures for surface modification and determination are the advantages of the prepared sensors.